Gambaran Faktor Risiko Kejadian TB Anak di Wilayah Kerja Puskesmas Kedungmundu - Azizah, Waviq; Martini, Martini; Fauzi, Muh; Adi, Mateus Sakundarno (Jurnal Riset Kesehatan Masyarakat, 2024)
Background: TB in children (TB cases that occur between the ages of 0-14 years) has a crucial role in TB control efforts. Child TB cases in the Kedungmundu Community Health Center working area experienced a significant increase from 2021 (14%) to 2023 (35%).This research was conducted to determine the risk factors for the incidence of TB in children in the Kedungmundu Community Health Center working area. Methods:  This research is a descriptive study with a case control study design, which was conducted in the Kedungmundu Community Health Center work area in March-April 2024. Results: This research shows that the type of respondent in the case group was more than male, parental income <UMK, lighting levels that did not meet the requirements, humidity levels that did not meet the requirements, and had a higher history of contact with TB sufferers. However, based on the research results, the case group has demonstrated good residential density and nutritional status.